Újszentiván lakosságának etnikai és felekezeti viszonyainak változásai - Miklós, Péter (Közép-Európai Közlemények, 2010)
Újszentiván is a village in Hungary (Csongrád County, near Szeged). The polulation of Újszentiván from 1783 (the data of Újszentiván’s refundation) to the first years of the 19th century was only Serbs. In the years of 1820-30’s we can observe the gradual settle down of Germans. These Germans came from the area of one-time Temesi Bánság (Temeswarer Banat). It wasn’t pimary migration (from Germany), only secondary.In 1880-90’s gained the Hungarians’ population is the village. After the First World War the grand part of local Serb community has gone to Serb-Croatian-Sloven Kingdom. After the Second World War (in 1946-47) the Germans in Újszentiván located out to West-Germany. In our days the population of Újszentiván near exclusively Hungarian.